2011
DOI: 10.1371/journal.pone.0027828
|View full text |Cite
|
Sign up to set email alerts
|

Nod2 Downregulates TLR2/1 Mediated IL1β Gene Expression in Mouse Peritoneal Macrophages

Abstract: Nod2 is a cytosolic pattern recognition receptor. It has been implicated in many inflammatory conditions. Its signaling has been suggested to modulate TLR responses in a variety of ways, yet little is known about the mechanistic details of the process. We show in this study that Nod2 knockdown mouse peritoneal macrophages secrete more IL1β than normal macrophages when stimulated with peptidoglycan (PGN). Muramyl dipeptide (MDP, a Nod2 ligand) + PGN co-stimulated macrophages have lower expression of IL1β than P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Although Gefitinib also suppresses EGFR signaling, taking all the data together, it is likely that NOD2 signaling (perhaps together with EGFR) suppresses production of at least a few chemokines and/or cytokines, perhaps to control inflammation mediated through TLRs. In fact, NOD2 has been shown to inhibit TLR2-mediated signaling in other studies [ 43 , 44 ], indicating that this possibility is viable. In one study, when splenocytes from NOD2-deficient mice were stimulated with peptidoglycan (PGN), a TLR2 ligand, the cytokine production was found to be higher than those from wild-type mice [ 44 ].…”
Section: Discussionmentioning
confidence: 96%
“…Although Gefitinib also suppresses EGFR signaling, taking all the data together, it is likely that NOD2 signaling (perhaps together with EGFR) suppresses production of at least a few chemokines and/or cytokines, perhaps to control inflammation mediated through TLRs. In fact, NOD2 has been shown to inhibit TLR2-mediated signaling in other studies [ 43 , 44 ], indicating that this possibility is viable. In one study, when splenocytes from NOD2-deficient mice were stimulated with peptidoglycan (PGN), a TLR2 ligand, the cytokine production was found to be higher than those from wild-type mice [ 44 ].…”
Section: Discussionmentioning
confidence: 96%
“…This usually implies inhibitory effects of NOD2 on TLR‐induced responses. In settings of simultaneous stimulus application, MDP at a concentration of 10 μg/ml has been reported to down‐regulate IL‐1β expression induced by a TLR2/1 agonist (peptidoglycan) in murine peritoneal macrophages in vitro; in the same study, MDP did not affect IL‐1β production induced by LPS (which was used at a high concentration of 1 μg/ml) and up‐regulated TLR2‐induced IL‐10 and TNF production . Watanabe et al.…”
Section: Descriptive Data On Nod‐tlr Interactionsmentioning
confidence: 90%
“…In settings of simultaneous stimulus application, MDP at a concentration of 10 g/ml has been reported to down-regulate IL-1 expression induced by a TLR2/1 agonist (peptidoglycan) in murine peritoneal macrophages in vitro; in the same study, MDP did not affect IL-1 production induced by LPS (which was used at a high concentration of 1 g/ml) and up-regulated TLR2-induced IL-10 and TNF production. 36 Watanabe et al reported that in murine splenic macrophages in vitro, MDP at 10-100 g/ml specifically down-regulated IL-12 production induced through TLR2 but not through several other TLRs. 37 To reconcile conflicting data about positive and negative effects of MDP on TLR-mediated activation, Borm et al showed that MDP at low concentrations (1-25 g/ml) augments TLR2-induced TNF production by monocytes, but at a high concentration (100 g/ml) suppresses it.…”
Section: Nod-tlr Antagonism and Cross-tolerancementioning
confidence: 99%
“…In agreement with our results, recent studies showed a synergic effect between NOD2 and TLR2 [48], where specific NOD2 activation with MDP increased the induction of TNFα, IL-1 and IL-10 upon co-stimulation with TLR2 agonists. Other studies showed that the activation of NOD2 could modify the expression of TLR2 negatively, although this seems to be determined by the different kinds of studied cells [49]. However, it seems that NOD2 could also recognize the specific bacterial fragments recognized by TLR2 heterodimers (TLR2/1 and TLR2/6) [50].…”
Section: Discussionmentioning
confidence: 98%